Ante-bellum Alabama : town and country - Jordan, Weymouth T., 1912-1968 (Library of Alabama classics., 1987)
Ante-Bellum Alabama: Town and Country was written to give the reader insight into importaant facers of Alabama's ante-bellum history. Presented in the form of case studies from the pre-Civil War period, the book deals with a city, a town, a planter's family, rural social life, attitudes concerning race, and Alabama's early agricultural and industrial development. Ante-bellum Alabama's primary interest was agriculture; the chief crop was King Cotton; and most of the people were agriculturalists. Towns and cities came into existence to supply the agricultural needs of the state and to proces.